2005
DOI: 10.1158/0008-5472.can-05-0036
|View full text |Cite|
|
Sign up to set email alerts
|

IFN-β Down-Regulates the Expression of DNA Repair Gene MGMT and Sensitizes Resistant Glioma Cells to Temozolomide

Abstract: Alkylating agents, such as temozolomide, are among the most effective cytotoxic agents used for malignant gliomas, but responses remain very poor. The DNA repair protein O 6 -methylguanine-DNA methyltransferase (MGMT) plays an important role in cellular resistance to alkylating agents. IFN-B can act as a drug sensitizer, enhancing toxicity against a variety of neoplasias, and is widely used in combination with other antitumor agents such as nitrosoureas. Here, we show that IFN-B sensitizes glioma cells that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 17 publications
5
142
0
2
Order By: Relevance
“…Previous evidence reported by our group and others has shown that IFN-β induced growth inhibition or apoptosis in a variety of neoplasms (12,(23)(24)(25). Recently, we reported that IFN-β induced the differentiation of GICs to cells with an oligodendrocyte-like phenotype (26).…”
Section: Ifn-β Downregulates Mir-21 Transcriptionmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous evidence reported by our group and others has shown that IFN-β induced growth inhibition or apoptosis in a variety of neoplasms (12,(23)(24)(25). Recently, we reported that IFN-β induced the differentiation of GICs to cells with an oligodendrocyte-like phenotype (26).…”
Section: Ifn-β Downregulates Mir-21 Transcriptionmentioning
confidence: 72%
“…The source of the cell lines and the culture conditions have been reported previously (23). Glioma tissue samples were obtained from patients (nos.…”
Section: Glioma Cell Lines and Primary Tumor Sphere Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, clinical research has revealed that the methylation status of the MGMT promoter is associated with the prognostic outcome of GBM patients treated with temozolomide (Hegi et al, 2005). Reduction of MGMT expression induced by p53 in GBM cells renders them sensitive to www.intechopen.com temozolomide (Natsume et al, 2005). It is reasonable to speculate that increased expression of p53 by GSK3 inhibition enhances temozolomide chemosensitivity through the reduction of MGMT (Miyashita et al, 2009a).…”
Section: Chemosensitivitymentioning
confidence: 99%
“…To date, a number of methods have been described to inhibit MGMT; however, their significance in clinical use for the purpose of overcoming temozolomide resistance is still limited or unknown [3,37,38]. Here, we have shown that the molecular pathway linking MEK to MGMT expression could offer novel and rational targets for MGMT inactivation, specifically MEK (by SL327) and MDM2 (by Nutlin-3).…”
Section: Resultsmentioning
confidence: 88%